2020
DOI: 10.1920/re.ifs.2020.0167
|View full text |Cite
|
Sign up to set email alerts
|

The impact of undergraduate degrees on lifetime earnings

Abstract: Conclusion 67 Bibliography 70 A More on the HESA data 72 B Lifetime exchequer receipts 76 C Median net lifetime returns 81 D Full subject results by age 84 E Average net lifetime returns with different discount rates 85

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Patients with a degree qualification preferred F2F over VC care. A report 23 concluded that both women and men with a degree are likely to have higher lifetime earnings than women and men without a degree (£252,000 more and £168,000 more respectively). The type of job an individual has may be dependent on employment status and those with lower education (up to A-Level in the United Kingdom) are over-represented in ‘zero hours’ contracts 24 and therefore unable to take paid leave for medical appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a degree qualification preferred F2F over VC care. A report 23 concluded that both women and men with a degree are likely to have higher lifetime earnings than women and men without a degree (£252,000 more and £168,000 more respectively). The type of job an individual has may be dependent on employment status and those with lower education (up to A-Level in the United Kingdom) are over-represented in ‘zero hours’ contracts 24 and therefore unable to take paid leave for medical appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining a university degree is linked with advanced career trajectories and high earnings across the lifespan (OECD, 2020), as well as with better health outcomes and longer life expectancy (Olshanky et al, 2012). Higher degree performance (Jones & Jackson, 1990) and university prestige (e.g., university league table ranking) are also related to increased earnings (Britton et al, 2020;Hoekstra, 2009). Obtaining higher-level vocational qualifications, such as advanced apprenticeships, support direct entry to the labour market in skills-based economies, facilitating advantageous employment opportunities (Hanushek et al, 2017;Kirby, 2015).…”
Section: Educational Outcomesmentioning
confidence: 99%
“…Girls tend to outperform boys on average throughout compulsory education and beyond (Voyer & Voyer, 2014). However, women are less likely than men to enter competitive professions with high salaries, and generally, they earn less than men (Britton et al, 2020;Shauman, 2006). Systematic gender differences have also been observed in social-emotional development during emerging adulthood (Conley et al, 2020;Galambos et al, 2006), but the evidence for gender as a moderator of the effects of school performance is fragmentary and inconsistent (Bücker et al, 2018;French et al, 2015;Huang, 2015).…”
mentioning
confidence: 99%